2021
DOI: 10.1007/s11102-021-01173-0
|View full text |Cite
|
Sign up to set email alerts
|

Safety of growth hormone (GH) treatment in GH deficient children and adults treated for cancer and non-malignant intracranial tumors—a review of research and clinical practice

Abstract: Individuals surviving cancer and brain tumors may experience growth hormone (GH) deficiency as a result of tumor growth, surgical resection and/or radiotherapy involving the hypothalamic-pituitary region. Given the pro-mitogenic and anti-apoptotic properties of GH and insulin-like growth factor-I, the safety of GH replacement in this population has raised hypothetical safety concerns that have been debated for decades. Data from multicenter studies with extended follow-up have generally not found significant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 180 publications
(322 reference statements)
0
30
0
Order By: Relevance
“…Nevertheless, in-vitro and in-vivo proliferative and pro-mitogenic properties of GH and insulin-like growth factor-I (IGF-I), which is produced following stimulation by GH, have raised concerns regarding potential associations between hGH use and the risk for tumor recurrence or subsequent malignancy in treated childhood cancer and brain tumor survivors. This concern has prompted the publication of over the past 3 decades many reports and reviews on the topic including a recent consensus statement from the GH Research Society (6,17).…”
Section: Safety Of Growth Hormone Replacementmentioning
confidence: 99%
See 4 more Smart Citations
“…Nevertheless, in-vitro and in-vivo proliferative and pro-mitogenic properties of GH and insulin-like growth factor-I (IGF-I), which is produced following stimulation by GH, have raised concerns regarding potential associations between hGH use and the risk for tumor recurrence or subsequent malignancy in treated childhood cancer and brain tumor survivors. This concern has prompted the publication of over the past 3 decades many reports and reviews on the topic including a recent consensus statement from the GH Research Society (6,17).…”
Section: Safety Of Growth Hormone Replacementmentioning
confidence: 99%
“…The primary limitation of the SAGhE cohort data is the reliance on comparison of adverse health outcomes and mortality among patients treated with hGH to data from the general population (27). The absence of a non-GH treated CCS control group curtails investigator ability to identify a specific effect of hGH, beyond risks that are already conferred by the primary cancer or tumor and their treatments (6). Nevertheless, a recent report from this cohort reassuringly showed that the occurrence of meningioma in CCS did not correlate with the dose or duration of treatment with hGH (26).…”
Section: Safety Of Growth Hormone Replacementmentioning
confidence: 99%
See 3 more Smart Citations